Modeling a DC to DC converter and design a controller for the converter - Haque, Ayman Mahmud; Sutradhar, Dipanwita; Islam, Md Istiakul; Ferdous, Zarmin (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.